2018
DOI: 10.1038/s41467-018-04794-5
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the structural characteristics of CaO and its effective stabilization yield high-capacity CO2 sorbents

Abstract: Calcium looping, a CO2 capture technique, may offer a mid-term if not near-term solution to mitigate climate change, triggered by the yet increasing anthropogenic CO2 emissions. A key requirement for the economic operation of calcium looping is the availability of highly effective CaO-based CO2 sorbents. Here we report a facile synthesis route that yields hollow, MgO-stabilized, CaO microspheres featuring highly porous multishelled morphologies. As a thermal stabilizer, MgO minimized the sintering-induced deca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
122
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 213 publications
(128 citation statements)
references
References 58 publications
5
122
0
1
Order By: Relevance
“…8, both Ca and Mg filed all the mapping images, revealing an inhomogeneous distribution of the stabilizer (MgO) within the active material (CaO). Previous researchers9,58 proposed that the carbon template could beneficial for the compositional homogeneity of its products. To confirm this hypothesis, XRD and XPS…”
mentioning
confidence: 99%
“…8, both Ca and Mg filed all the mapping images, revealing an inhomogeneous distribution of the stabilizer (MgO) within the active material (CaO). Previous researchers9,58 proposed that the carbon template could beneficial for the compositional homogeneity of its products. To confirm this hypothesis, XRD and XPS…”
mentioning
confidence: 99%
“…It is well known that the carbonation reaction consists of two stages: an initial rapid kinetically-controlled stage, followed by a substantially slower diffusion-controlled stage. [41][42][43] Considering This advantage was experimentally confirmed by Naeem et al, 44 who used in-situ TEM to observe the morphological changes of CaO hollow microspheres during the calcination reaction, and found although the molar volume of CaCO3 is more than twice as high as that of CaO, the shrinkage in the diameter of the microsphere after calcination was determined to be <15%, which was due to the presence of the central void within the multi-shell architecture. Moreover, the presence of highly porous shells would allow rapid transport of CO2 to and from the material.…”
Section: Resultsmentioning
confidence: 68%
“…39,45,46 It should also be noted that the shells are composed of CaO and CuO (or CaO, CuO and calcium copper oxide) nano-sized particles, among which CaO nanoparticles minimize the diffusion distance of CO2 through the freshly formed CaCO3 product layer in the diffusion-controlled stage during the carbonation reaction. 44 Furthermore, the three-dimensional hollow microsphere structures realize a physical separation of the nanoparticles, which is expected to effectively mitigate particle/grain agglomeration. 47 Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…Commonly used stabilizers can be classied into two different groups: (i) those forming a mixed oxide with CaO, such as Al 2 O 3 , SiO 2 , TiO 2 and ZrO 2 , [23][24][25][26] and (ii) inert stabilizers that do not react chemically with CaO under the relevant operating conditions, such as MgO, Y 2 O 3 , and ZnO. [27][28][29][30][31] Furthermore, to make calcium looping a viable option at the industrial scale (e.g., operation in circulating uidized beds) high CO 2 uptakes within relatively short residence times are required. The carbonation of CaO is known to proceed in two reaction regimes, 32,33 viz., the kinetically controlled carbonation followed by a sluggish diffusion-limited carbonation regime (the diffusivity of CO 2 in the CaCO 3 product layer, D CaCO 3 ¼ 0.003 cm 2 s À1 , is two orders of magnitude smaller than that in CaO, D CaO ¼ 0.3 cm 2 s À1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the ideal CaO-based sorbent would exhibit a nanostructured and highly porous morphology that is stabilized by a high-T T temperature material. Previous studies 25,28,[34][35][36] have revealed that the scale (micro-, nano-or even atomic level) at which the stabilizer is introduced into the matrix plays an important role for the overall performance of the sorbents. A number of techniques have been adopted to introduce a stabilizer into the CaO including wet-mixing, 37 coprecipitation, 38 hydration, 39 ame spray pyrolysis, 40 hydrolysis 41 and sol-gel.…”
Section: Introductionmentioning
confidence: 99%